Bonner Kunstverein Jahresgaben 1985. - Bonner Kunstverein, Bonn (Bonn : Bonner Kunstverein, 1985)
Gläsker, Horst ; Hadersdorfer, Doris ; Hallmann, Blalla W. ; von Hasselbach, Tinka ; Hien, Albert ; Huber, Stephan ; Huber, Thomas ; Meistermann, Georg ; Oppermann, Anna ; Pflaumann, Volker ; Pohl, Marianne ; Reins, Arno ; Rieger, Helmut ; De Saint-Pahlle, Niki ; Schwegler, Fritz ; Spoerri, Daniel ; Virnich, Thomas
Duits
boek